Efeitos adversos da poliquimioterapia para hanseníase - Kubota, Rosina Maria Martins (2012)
Introduction: Multidrug therapy (MDT/WHO) forthe treatment of Leprosy´s can cause adverse effects related to Rifampicin (RMP) or Dapsone (DDS). These effects can change the therapeutic regimen. Objectives: To identify the causes of change intreatment and to evaluate the clinical dermatologica and conditions of patients who underwent alternative therapy. Method: A prospective, descriptive and cross-sectional study with instrument divided into pre and post discharge. Out of 182 patients treated between1995 to 2007with MDT/WHO; 34(18.7%) underwent alternative doses and of these, 21were located for the interview Chi-Square test with p-value<0.05 was used. Results: The sample comprised: all married, 40 to59 years, low socioeconomic and educational status. Paucibacillary (PB) and multibacillary (MB) patients without using DDS and RMP had as negative the last bacilloscopy (>50%), and the positive results of the others showed slow involution. The most frequent incidence according to clinical form was lepromatous in the intolerant to DDS and borderline leprosy in the ones without RMP. Adverse effects mostly accounted MB patients and appeared between 1-2months. According to 73.5% of the DDS intolerant, the change of the therapeutic regimen was related with hematological causes (48.5%), and the ones to RPM (26.5%) with hepatological problems (50%). In the post-discharge assessment, the nodules and plaques have disappeared and the amount of spots increased (p<0.05). Neural lesions, orpain in the limbs were developed, sensitivity and muscle strength diminished, and claw toes (p<0.05) appeared. Conclusion: The development of disability revealed the need of monitoring carefully the neural function in cases of discharge.